A 64-channel high-time resolution digital waveform sampling electronic system based on DRS4 for positron burst annihilation lifetime measurement. (1st October 2022) - Wang, M.; Bian, Z.; Wang, Y.; Li, D.; Li, X.; Cai, J.; Wang, P.; Wang, B.; Cao, X.; Zhang, Z.; Kuang, P.; Liu, F.; et al.
Abstract: Measurements of the positron burst annihilation lifetime place high demand on the time discrimination of electronics. DRS4 chips based on switched capacitor array technology (SCA) are used to develop an electronic system with a total (2048 + 256)-channel sampling rate up to 5.12 GSPS, which can provide better time resolution and flexible data processing. The electronic system is modular in design and includes a front-end waveform sampling module (WSM) with 32 waveform sampling boards, each with 64 input channels plus 8 additional channels(one per DRS4 chip) for time calibaion, in addition to a back-end data processing module (DPM). The fan-out circuit integrated with the DPM will fan out the T0 signal in multiple stages at the time of positron burst generation and provide a common starting time and trigger signal for every DRS4 chip in the WSM. In this electronic system, the jitter of T0 after three-stage fan-out is 18 ps. After DC offset correction and time interval nonuniformity calibration, the coincidence time resolution with other channels is about 21 ps (σ). In addition, we correct the time difference of different channels of different chips, which is caused by different trace lengths of the multi-level fan-out T0 signal and the different fabrication processes. The electronic system is used to evaluate a 64-pixel detector module, and the time resolution of the detection module is measured to be 44 ps (σ).